Laparoscopic Approach in Correction of Adult Diaphragmatic Morgagni Hernia - Mazni, Yarman; Prabowo, Andrio W (UI Scholars Hub, 2018)
Introduction. Adult diaphragmatic hernia of Morgagni is a very rare congenital anomaly. Therefore, to date there is no standard surgical techniques used in the management. Thus, a systematic review aimed to find the highest evidence in the management. Method. A systematic review conducted in accordance with PRISMA. Literature search proceeded on PubMed and ScienceDirect using keywords